Multiple typical ranks in matrix completion - Dressler, Mareike; Krone, Robert (Linear algebra and its applications, 2025)
Low-rank matrix completion addresses the problem of completing a matrix from a certain set of generic specified entries. Over the complex numbers a matrix with a given entry pattern can be uniquely completed to a specific rank, called the generic completion rank. Completions over the reals may generically have multiple completion ranks, called typical ranks. We demonstrate techniques for proving that many sets of specified entries have only one typical rank, and show other families with two typical ranks, specifically focusing on entry sets represented by circulant graphs. This generalizes the results of Bernstein, Blekherman, and Sinn. In particular, we provide a complete characterization of the set of unspecified entries of an n×n matrix such that n−1 is a typical rank and fully determine the typical ranks of an n×n matrix with unspecified diagonal for n<9. Moreover, we study the asymptotic behavior of typical ranks and present results regarding unique matrix completions.